2014
DOI: 10.1177/0954411914546562
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an optical system to measure acetabular shell deformation in cadavers

Abstract: Deformation of the acetabular shell at the time of surgery can result in poor performance and early failure of the hip replacement. The study aim was to validate an ATOS III Triple Scan optical measurement system against a co-ordinate measuring machine using in vitro testing and to check repeatability under cadaver laboratory conditions. Two sizes of custom-made acetabular shells were deformed using a uniaxial/two-point loading frame and measured at different loads. Roundness measurements were performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
0
33
1
Order By: Relevance
“…Each IOS scan file was imported then superimposed onto the reference model, using an Initial Alignment and a Best Fit Alignment , considering only the segmented typodont teeth (Figure ). The software's Best Fit Alignment function aligns the test file, and reference file using an iterative closest point algorithm, which has become a standard method for aligning digital 3D files …”
Section: Methodsmentioning
confidence: 76%
“…Each IOS scan file was imported then superimposed onto the reference model, using an Initial Alignment and a Best Fit Alignment , considering only the segmented typodont teeth (Figure ). The software's Best Fit Alignment function aligns the test file, and reference file using an iterative closest point algorithm, which has become a standard method for aligning digital 3D files …”
Section: Methodsmentioning
confidence: 76%
“…This blue light scanner uses multiple camera sources to record the features of the object being scanned. It has been shown to be able to capture data with a very high precision and an accuracy of 3 μm for a jaw sized scan …”
Section: Methodsmentioning
confidence: 99%
“…A master scan of this model was made to fabricate the master digital model, against which the different scan patterns would be compared for trueness and precision. This scan was taken using ATOS Triple Scan (GOM technologies, Santa Ana, CA), an industrial grade, blue‐light 3D scanner that has been shown to be accurate to 3 μm . This produced a master stereolithography (.stl) file that, when imported into a three‐dimensional (3D) analysis software Geomagic Control (3D Systems, Rock Hill, SC), allowed for alignment of experimental and control .stl files by highest average nodal data‐point overlay; and graphic comparison of the separate scan patterns (Figure ).…”
Section: Methodsmentioning
confidence: 99%